Historia regionu siedleckiego w publikacjach wydanych po 2013 r. (PDF 2,67 MB) (Książnica Śląska, 2025)
The author presents publications related to the Siedlce region ina broad historical context. After reflections on the region and regionalism, he describes the territorial and administrative changesin southern Podlasie. First of all are presented bibliographic publications and regional scientific journals. Then he brings up worksabout religion, art and the most valuable monuments. The writer focuses above all on the presentation of publications on the history ofSiedlce and the cities of the region in various historical periods: fromthe 16th century to World War II and the first post-war years. Theauthor’s main interest is in publications published by local institutions (libraries, museums) and enthusiasts of regional history.